Cardiotoxicity of lung cancer-related immunotherapy versus chemotherapy: a systematic review and network meta-analysis of randomized controlled trials - Jin, Chengwei; Qi, Jia; Wang, Qilei; Pu, Chenwei; Tan, Mingming (Frontiers in Oncology, 2023)
Background This was despite previous clinical randomized controlled trials (RCTs) that have tested immune checkpoint inhibitors (ICIs) to cause a variety of toxicities in cancer treatment.The effects of different ICIs alone or in combination with chemotherapy on cardiotoxicity remain controversial. In this study, we aimed to evaluate the cardiotoxicity of PD-1(programmed cell death protein 1), PD-L1(programmed cell death-Ligand 1), CTLA-4(cytotoxic T lymphocyte associate protein-4) combined chemotherapy on lung cancer. Methods We included the following ICI: Durvalumab, Avelumab, Ipilimumab, Atezolizumab, Pembrolizumab, Cemiplimab, Nivolumab. Data extraction tables were used to extract information about the trials and the Cochrane Bias Risk Tool was used to assess the risk of bias for each RCTS. The main outcomes were hypertension, heart failure, pericardial effusion and other adverse cardiac events. A random effects model was used for the meta-analysis, followed by a network meta-analysis within a Bayesian framework. Results Seventeen RCTs were included, with a total of 11,063 people in the experimental and control groups, with an average age greater than 60 years. Based on the evaluation of all drug classes in RCTs, CTLA-4+chemotherapy (OR, -0.69 [95%CI, 2.91-1.52] and PD-L1 (OR, -0.21 [95%CI, -1.03-0.60]), was less cardiotoxic than control arm and appeared to be a safer option for adverse cardiac events. PD-L1 alone was less cardiotoxic than PD-1 alone (OR, -0.57 [95%CI, -1.96-0.82]). The dual immunotarget inhibitor PD-1+CTLA-4 had the lowest SUCRA value and appeared to have the highest cardiotoxicity (SUCRA=9). Conclusion According to the classification of drug types, CTLA-4+chemotherapy had fewer adverse cardiac events compared with other combination therapies. Dual immunotarget inhibitors were more likely to have adverse cardiac reactions. Therefore, clinicians should consider this evidence when developing an ICI immunotherapy regimen for lung cancer.